1991
DOI: 10.1111/j.1365-3040.1991.tb00966.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of photosynthesis and carbohydrate‐partitioning to limitations in nitrogen and water availability in field‐grown sunflower*

Abstract: Abstract. Sunflower plants (Helianthus annuus L., cv. CGL 208) were field‐grown in adjacent plots of varying resource availability. Control plants received irrigation (on a 4–5 d interval) and high levels of fertilizer nitrogen. Nutrient‐stress (N‐stress) plants received control levels of irrigation but no nutrient amendments and were determined to be nitrogen‐limited. Water‐stress (H2O‐stress) plants received control levels of fertilizer nitrogen, but no irrigation after approximately 6 weeks of plant growth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
2
4

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(58 citation statements)
references
References 37 publications
7
45
2
4
Order By: Relevance
“…This result contrasted with the lack of drought effects on hexose in grapevine (Rodrigues et al, 1993), but was similar to the seven-to 14-fold increase in glucose concentration in sunflower leaves observed by Fredeen et al (1991). Despite a significant decrease in sucrose concentration, total soluble carbohydrates (sucrose + glucose + fructose) greatly increased in water-stressed plants (+76%).…”
Section: Introductioncontrasting
confidence: 52%
See 1 more Smart Citation
“…This result contrasted with the lack of drought effects on hexose in grapevine (Rodrigues et al, 1993), but was similar to the seven-to 14-fold increase in glucose concentration in sunflower leaves observed by Fredeen et al (1991). Despite a significant decrease in sucrose concentration, total soluble carbohydrates (sucrose + glucose + fructose) greatly increased in water-stressed plants (+76%).…”
Section: Introductioncontrasting
confidence: 52%
“…5.3.1.9) and then into 6-phosphogluconate by glucose-6-P deshydrogenase (E.C. (Bensari et al, 1990;Fredeen et al, 1991;Quick et al, 1992) or remained at levels close to those of control plants in lupin or grapevine (Quick et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that leaf N concentration was not the only factor contributing to the greater effects on growth responses between unfertilized and fertilized seedlings. Freeden et al [18] suggested that the photosynthetic process is down-regulated under conditions of N limitation. In our study, the observed decline in g s in unfertilized seedlings resulted in reduced CO 2 assimilation rates.…”
Section: Leaf Physiology and Nutritional Responsesmentioning
confidence: 99%
“…In citrus plants, Syvertsen, Smith e Boman (1993) observed that N concentration decreased as Cl -concentrations increased in the leaves; however, Lea-Cox and Syvertsen (1993) reported that foliar N application increased photosynthesis rate in citrus plants subjected to saline stress. Greater stomatal resistance was observed in plants cultivated under low N conditions, and the authors concluded that the decrease in photosynthesis was caused by the inhibition of the activity of the RuBP enzyme (Ribulose-1,5-bisphosphate carboxylase/oxygenase) (FREDEEN; GAMON;FIED, 1991).…”
Section: Experiments II -Nitrogen Fertilization As Attenuator Of Salinmentioning
confidence: 99%